THE INTERPLAY BETWEEN ORAL HEALTH, SYSTEMIC FRAILTY, AND QUALITY OF LIFE IN THE AGING POPULATION: A COMPREHENSIVE REVIEW OF RECENT ADVANCEMENTS (2009–2025) - Susanna Halim; Diana Mayleen Halim (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The intersection of natural oral aging with severe conditions like periodontitis, chronic xerostomia, and tooth loss significantly compromises geriatric well-being and systemic health. National screening data from 2025 emphasizes this crisis, revealing that approximately 37 percent of the population under sixty has already experienced tooth loss, indicating a broader global public concern. This systematic review comprehensively evaluates the precise impact of physiological aging on hard oral structures, edentulism-related frailty, microbiota balance, and psychosocial prosthetic rehabilitation outcomes. The methodology involved an exhaustive screening and qualitative synthesis of contemporary scientific literature, including clinical trials and observational analyses published between 2009 and 2025. The findings indicate that senescence induces cumulative alveolar bone depletion, enamel thinning, and salivary gland hypofunction, which collectively increase overall malnutrition risks and poor nutritional intake. Crucially, edentulism directly accelerates physical frailty, particularly in older individuals with fewer than 20 functional teeth, while altering oral-gut microbial homeostasis. Conversely, timely oral rehabilitation via implants or removable dentures restores masticatory efficiency and psychological wellness, substantially upgrading quality of life. The main conclusion asserts that severe oral deterioration is largely preventable; integrated overall geriatric care prioritizing the preservation of 20 remaining teeth and vital long-term prosthetic restoration is paramount to mitigating physical decline.